Equality of Rights and Courts: Constitutional-Based Arguments on the Fixed-Standard of Minimum Age for Marriage in Lights of Maqāshid al-Syarīah (Mazahib, 2021)
This study presents the dynamics of constitutional-based arguments in the discourse of fixed-standard of minimum age for marriage through the judicial review mechanism at the Constitutional Court. Two decisions contain this provision. In the first decision (No. 30-74/PUU/XII/2014), the Court rejected reviewing the law. Meanwhile, the Court partially granted the request in the second decision (No. 27/PUU/XV/2017). This study aims to analyze the dynamics of changes in these provisions: constitutional-based arguments and their logic of legal reasoning. This article is written by applying a case and conceptual approach. Legal cases are derived from several documents analyzed using ideas and theories of teleological dimensions in Islamic law. The study results revealed that the change in the provisions was caused by differences in the Judge’s legal considerations in the two Court decisions resulting from different philosophical perspectives originating from the articles of legal texts. Those considerations and changes are in accordance with maqāshid al- syarī’ah: the efforts to fulfill the protection of the soul (hifẓ al- nafs), property (hifẓ al- māl), and honor (hifẓ al- irdh). Keywords Equality of Rights, Legal Reasoning, Constitutional Court, Minimum Age For Marriage, Maqāshid al- Syarī’ah.